Citizenship, Participation, and Public Interest in Public Communication: A Case Study - Sena, Karita Emanuelle Ribeiro [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
This article aims to identify ways of materializing the principles of Public Communication in real projects. Through Content Analysis, we seek to verify the materialization of three principles: Citizenship, Participation, and Public Interest. Projects were selected from entities representing each of the potentially promoting actors of Public Communication: State, civil society, and private organization: Fala.BR (Federal Comptroller General's Office); Operation Serenata de Amor (Open Knowledge Brasil); and Guia do Voto (Votorantim), respectively. We identified thatthe main principle of Public Communication addressed is Participation, while Citizenship is primarily highlighted by Fala.BR/CGU, and Public Interest receives relatively little attention, almost reaching a total absence of references in the discursive field.
Keywords: Public Communication; Citizenship; Participation; Public Interest